Modified naphthol resin, method for producing the same, and resin composition containing the same

The modified naphthol resin addresses the reactivity and processability issues of common substrate materials by introducing a terminal alkenyl group through chlorination and grafting, enhancing thermal stability and dielectric properties for electronic components.

JP2025009705AInactive Publication Date: 2025-01-20NANYA PLASTICS CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023197227
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-29
Filing Date
2023-11-21
Publication Date
2025-01-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Common substrate materials like polyphenylene ether resins and cyanate resins exhibit high reactivity and fast reaction rates, making it difficult to measure the gel point and compromising processability, which are essential for dielectric properties and heat resistance required in electronic components.

Method used

A modified naphthol resin is produced through chlorination and chemical grafting to introduce a terminal alkenyl group, resulting in improved properties such as increased glass transition temperature, lower dielectric constant and dissipation factor, and better processability.

Benefits of technology

The modified naphthol resin enhances thermal stability, reduces thermal expansion, improves peel strength, and decreases water absorption, thereby meeting the demands of high-frequency signal transmission and heat resistance in electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009705000001_ABST
    Figure 2025009705000001_ABST
Patent Text Reader

Abstract

To provide a resin composition containing a modified naphthol resin excellent in processability.SOLUTION: A modified naphthol resin has a structure represented by the following [Formula 3]. In the [Formula 3], V is a vinyl group, an allyl group or an isopropenyl group, L is a connection group having a double bond, and n is a positive integer of 2 to 40.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin and a method for producing the same, and more particularly to a modified naphthol resin and a method for producing the same. [Background technology]

[0002] With the advancement of science and technology, electronic components are becoming lighter, thinner, shorter and smaller. In addition, with the emergence of the fifth generation mobile network (5G for short), the industry demand for high frequency transmission, high speed signal transmission and low latency continues to grow. Therefore, at present, related fields are promoting the development of substrate materials with high glass transition temperature (Tg), low dielectric constant (Dk), low dielectric tangent (Df) and good heat resistance to meet the needs of dielectric properties (low dielectric constant, low dielectric tangent) and heat resistance of electronic substrates. Summary of the Invention [Problem to be solved by the invention]

[0003] Common substrate materials include, for example, polyphenylene ether resin and cyanate resin, which have good dielectric properties, but have the disadvantages of being difficult to measure the gel point and poor processability due to their high reactivity and fast reaction rate. [Means for solving the problem]

[0004] The present invention provides a modified naphthol resin, a method for producing the same, and a resin composition containing the modified naphthol resin.

[0005] The method for producing the modified naphthol resin of the present invention includes the steps of subjecting a naphthol resin to a salification and chemical grafting reaction to form a modified naphthol resin having terminal alkenyl groups in the structure. The reagent used in the chemical grafting reaction has terminal alkenyl groups.

[0006] The modified naphthol resin of the present invention has a structure represented by formula 3 in this specification.

[0007] The resin composition of the present invention contains the above-mentioned modified naphthol resin.

[0008] The electronic device of the present invention includes a film layer formed from the above-mentioned resin composition. Effect of the Invention

[0009] Based on the above, the application of modified naphthol resins is better in terms of increasing glass transition temperature, decreasing thermal expansion coefficient, increasing peel strength, decreasing water absorption, and / or decreasing Dk / Df. [Brief description of the drawings]

[0010] [Figure 1] 1 is a schematic flow chart of a method for producing a modified naphthol resin according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In the following detailed description, for purposes of illustration and not limitation, exemplary embodiments disclosing specific details are set forth in order to provide a thorough understanding of various principles of the present invention. However, it will be apparent to one of ordinary skill in the art having the benefit of this disclosure that the present invention may be practiced in other embodiments that depart from the specific details disclosed herein. Moreover, descriptions of well-known devices, methods and materials may be omitted so as not to obscure the description of various principles of the present invention.

[0012] Ranges may be expressed herein as from "about" one particular value to "about" another particular value, or may be expressed directly as the one particular value and / or the other particular value. When a range is expressed, another embodiment includes from the one particular value and / or to the other particular value. Similarly, when values ​​are expressed as approximations, by use of the antecedent "about," it is understood that the particular value forms another embodiment. It is further understood that the endpoints of each range are either explicitly related to the other endpoint, or independent of the other endpoint.

[0013] As used herein, non-limiting terms (such as can, possible, or other similar terms) refer to optional or alternative implementations, inclusions, additions, or presence.

[0014] Unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. Terms (such as those defined in commonly used dictionaries) should be interpreted to have a meaning consistent with the meaning in the relevant technical context, and should not be interpreted in an idealized or overly formal sense unless expressly defined.

[0015] 1, the method for producing modified naphthol resin includes the following steps: Step S10: Prepare unmodified naphthol resin; Step S20: Salify and chemically graft the unmodified naphthol resin to form a modified naphthol resin.

[0016] <Unmodified naphthol resin>

[0017] In one embodiment, the unmodified naphthol resin may be substituted with only hydrogen or with alkyl groups having 1 to 5 carbon atoms (counted as C1 to C5) on the corresponding naphthol groups. The naphthol groups include 1-naphthol or 2-naphthol.

[0018] In one embodiment, the unmodified naphthol resin may have no nitro, nitroso, or amine groups on the corresponding naphthol groups. In one embodiment, the unmodified naphthol resin has no nitro, nitroso, or amine groups.

[0019] In one embodiment, the chemical formula of the unmodified naphthol resin can be represented by the following formula 1. [ka]

[0020] In formula 1, n may be a positive integer of 2 to 40.

[0021] In one embodiment, the chemical formula of the unmodified naphthol resin may be the same as [Formula 1]. For example, the hydrogen atom bonded to the carbon atom may be substituted with an alkyl group having 1 to 5 carbon atoms (counted as C1 to C5). As another example, the hydroxyl group in the naphthol group may be located at other substitution positions.

[0022] In one embodiment, the number average molecular weight (Mn) or weight average molecular weight (Mw) of the polymer can be measured by gel permeation chromatography (GPC).

[0023] In one embodiment, the number average molecular weight or weight average molecular weight is used for the estimation, and the average value of n may range from 1-30.

[0024] In one embodiment, the unmodified naphthol resin is commercially available (eg, ResiCare® 4000 from Shanghai Hengfeng New Materials Technology Co., Ltd.) or may be included in a commercially available product.

[0025] <Chlorination of unmodified naphthol resin>

[0026] In one embodiment, the unmodified naphthol resin represented by formula 1 may be subjected to an appropriate reaction to ionize the terminal hydroxyl groups of the naphthol groups so that the terminal hydroxyl groups are suitable for a subsequent reaction (eg, a chemical grafting reaction).

[0027] In one embodiment, the terminal hydroxyl group of the naphthol group may be ionized by a suitable alkaline solution, so that the terminal hydroxyl group of the naphthol group can become the corresponding salt, also called a salt.

[0028] In one embodiment, the alkaline solution may include a solution containing alkali metal ions or alkaline earth metal ions, preferably an alkali metal ion. Cations with a valence of +3 or higher may cause undesirable side reactions. For example, the alkaline solution may include sodium hydroxide, potassium hydroxide, sodium bicarbonate, potassium bicarbonate, sodium carbonate, potassium carbonate, or a mixture of the above dissolved in a suitable solvent (water, alcohol-water mixture, etc.).

[0029] In one embodiment, the pH value of the alkaline solution and / or the mole number of hydroxyl ions therein may be appropriately adjusted according to the total mole number of hydroxyl groups in the naphthol resin.

[0030] In one embodiment, based on the composition of the original reactants, the ratio of the total moles of hydroxyl groups in the naphthol resin to the moles of hydroxyl ions in the alkaline solution may be about 1:200 to 1:500, preferably about 1:250 to 1:400, more preferably about 1:300 to 1:350. If the moles or concentration of hydroxide ions are too low, the reaction may proceed slowly or the production rate may decrease. If the moles or concentration of hydroxide ions are excessive, undesirable side reactions may occur.

[0031] In one embodiment, the salified unmodified naphthol resin can be represented by the following formula 2: [ka]

[0032] In [Formula 2], the definition of n is basically the same as the corresponding definition of n in [Formula 1]. The reason why "the definition of n is basically the same" is stated above and below is because in chemical reactions, unintended but unpredictable and / or unavoidable side reactions may occur.

[0033] As shown in [Formula 2], the terminal hydroxyl group of the naphthol group of the unmodified naphthol resin may be ionized, as compared with the unmodified naphthol resin that has not been salified.

[0034] In one embodiment, the salified unmodified naphthol resins may have higher water solubility and / or higher reactivity compared to the non-salinated unmodified naphthol resins.

[0035] In one embodiment, during the process of ionizing the terminal hydroxyl group of the naphthol group, a suitable amount of catalyst may be added. In one embodiment, the catalyst may be, for example, quaternary ammonium compounds (QACs). For example, the catalyst may be tetrabutylammonium bromide (TBAB), tetraethylammonium bromide (TEAB), etc. The quaternary ammonium compounds may provide good interfacial activity to the reactants and / or increase the phase transition rate.

[0036] <Chemical grafting reaction>

[0037] For unmodified naphthol resin after salification, the ionized terminal hydroxyl group may be regarded as a nucleophile. Thus, for unmodified naphthol resin after salification, the ionized terminal hydroxyl group can be grafted and replaced by nucleophilic substitution for the corresponding modification.

[0038] The graft-substituted modified naphthol resin can be represented by the following formula 3. [ka]

[0039] In the formula [Formula 3], the definition of n is basically the same as the definition of n in the corresponding [Formula 1] and / or [Formula 2].

[0040] In the formula 3, V may be a functional group having a terminal alkenyl group. In one embodiment, V may be a functional group having 2 to 3 carbon atoms and having a terminal alkenyl group. In one embodiment, V may be a vinyl group, an allyl group, or an isopropenyl group. In one embodiment, V may be a vinyl group or an isopropenyl group. That is, the modified naphthol resin has a terminal alkenyl group.

[0041] In [Formula 3], L is a linking group having a double bond. In one embodiment, L may be a linking group having 1 to 11 carbon atoms and having at least a double bond. In one embodiment, L may be a ketone group, an alkyl-substituted or unsubstituted phenylene group, or an alkyl-substituted or unsubstituted methylbenzyl group. In one embodiment, L may be a ketone group, or an alkyl-substituted or unsubstituted methylbenzyl group. In one embodiment, L may be a ketone group or a methylbenzyl group. The "alkyl substitution" described above or below may be one in which at least one hydrogen is replaced with an alkyl group having 1 to 5 carbon atoms (counted as C1 to C5).

[0042] In one embodiment, the electrophile used in the chemical grafting reaction is a monomer molecule having a terminal alkenyl group. The monomer molecule may include a halide, an alkene halide, or an anhydrous alkene.

[0043] In one embodiment, the monomer molecule may include halomethylstyrene. Taking 4-halomethylstyrene as an example, it can be represented by the following formula 4: [ka]

[0044] In formula 4, X may be a fluorine group, a chlorine group, a bromine group, or an iodine group. X is preferably chlorine (i.e., chloromethylstyrene).

[0045] In one embodiment, the monomer molecule may include acrylic anhydride represented by the following formula 5: [ka]

[0046] In one embodiment, the monomer molecule may include methacrylic anhydride represented by the following formula (6): [ka]

[0047] In one embodiment, the monomer molecule may include methacryloyl chloride represented by the following formula (7): [ka]

[0048] In one embodiment, taking a monomer molecule of 4-halomethylstyrene as an example, the modified naphthol resin can be represented by the following formula 8. [ka]

[0049] In [Formula 8], the definition of n is basically the same as the definition of n in the corresponding [Formula 1] and / or [Formula 2].

[0050] In one embodiment, taking a monomer molecule of methacrylic anhydride or methacryloyl chloride as an example, the modified naphthol resin can be represented by the following formula (9). [ka]

[0051] In [Formula 9], the definition of n is the same as the definition of n in the corresponding [Formula 1] and / or [Formula 2].

[0052] <Applications of modified naphthol resin>

[0053] The modified naphthol resin represented by [Formula 8] or [Formula 9] may have lower dielectric properties, a higher glass transition temperature (Tg), a lower coefficient of thermal expansion (CTE), and / or better heat resistance, and therefore the modified naphthol resin represented by [Formula 8] or [Formula 9] may be suitable for application to electronic products.

[0054] The modified naphthol resin represented by [Formula 8] or [Formula 9] is easily soluble in common organic solvents (e.g., toluene, methyl ethyl ketone (MEK), etc.), and therefore the modified naphthol resin represented by [Formula 8] or [Formula 9] is easier to use.

[0055] In one embodiment, the modified naphthol resin represented by [Formula 8] or [Formula 9] may have better dielectric properties, heat resistance, flame retardancy, low moisture absorption, and / or adhesion in the application of electronic products.

[0056] In one embodiment, the resin composition may contain the modified naphthol resin of the above embodiment. For example, the basic formulation of the resin composition (i.e., the entire resin composition) contains at least the modified naphthol resin of the above embodiment.

[0057] In one embodiment, the modified naphthol resin may be 30 parts by weight (wt %) to 60 parts by weight, preferably 40 parts by weight to 50 parts by weight, based on 100 parts by weight of the basic formulation in the resin composition (ie, the entire resin composition).

[0058] In one embodiment, the basic composition of the resin composition may further include a bismaleimide resin. In one embodiment, the bismaleimide resin may be 10 parts by weight (wt%) to 30 parts by weight, preferably 15 parts by weight to 25 parts by weight, based on 100 parts by weight of the basic composition in the resin composition.

[0059] In one embodiment, the basic formulation of the resin composition may further include another polymer. In one embodiment, the other polymer may be 20 parts by weight (wt%) to 50 parts by weight, preferably 30 parts by weight to 40 parts by weight, based on 100 parts by weight of the basic formulation in the resin composition.

[0060] In one embodiment, the other polymer is not a naphthol resin (whether modified or not). In one embodiment, the other polymer does not have naphthol groups. In one embodiment, the other polymer does not have functional groups derived from naphthol groups (e.g., chlorinated, esterified, or etherified naphthol groups). In one embodiment, the other polymer may include a styrene / butadiene copolymer (such as poly(styrene-butadiene-styrene) (SBS)) or a derivative thereof. Styrene / butadiene copolymers or derivatives thereof are commercially available (e.g., TSRC, LCY Chemical Corp, Nippon Soda) and are often referred to as synthetic rubber.

[0061] In one embodiment, the resin composition may further include additives that are substantially free of resins, polymers, etc. The additives may include, for example, flame retardants, inorganic fillers, or combinations of the above.

[0062] In one embodiment, the addition of a flame retardant can improve the flame retardancy or fire resistance of the resin composition. In this specification, "flame resistant" or "flame retardant" means that the referenced object (e.g., film, layer, or structure) can pass the flame retardancy criteria of a standard test method. For example, take the UL94 Plastic Flammability Standard (flammability test for plastic materials for parts of equipment and household appliances) published by Underwriters Laboratories Inc. (UL) as an example, which is at least HB level.

[0063] In one embodiment, the flame retardant includes a brominated flame retardant, a phosphorus-based flame retardant, or a combination thereof.

[0064] In one embodiment, the viscosity of the resin composition can be increased by adding inorganic filler.For example, the inorganic filler can be silica, titanium dioxide, aluminum hydroxide, aluminum oxide, magnesium hydroxide, magnesium oxide, calcium carbonate, boron oxide, calcium oxide, strontium titanate, barium titanate, calcium titanate, magnesium titanate, boron nitride, aluminum nitride, silicon carbide, cerium dioxide, or a combination thereof.

[0065] In one embodiment, the silica used as the inorganic filler includes fused silica or crystalline silica. In one embodiment, fused silica is more preferred in consideration of the dielectric properties when applied to the copper foil substrate.

[0066] In one embodiment, the titanium dioxide used as the inorganic filler may include titanium dioxide having a rutile, anatase, or brookite structure. In one embodiment, titanium dioxide having a rutile structure is more preferred in consideration of the dielectric properties when applied to a copper foil substrate.

[0067] In one embodiment, based on 100 parts by weight of the basic formulation in the resin composition, the flame retardant may be further added in an amount of 20 parts by weight to 40 parts by weight, which can be calculated as 20 PHR (parts per hundred parts of resin) to 40 PHR, and approximately 25 PHR to 35 PHR is preferable.

[0068] In one embodiment, based on 100 parts by weight of the basic formulation in the resin composition, the inorganic filler may be further added in an amount of 50 parts by weight to 70 parts by weight, which can be calculated as 50 PHR to 70 PHR, and about 55 PHR to 65 PHR is preferable.

[0069] In one embodiment, the resin composition can be used in the manufacture of electronic devices, such as, but not limited to, copper foil boards or printed circuit boards.

[0070] <Manufacturing of copper foil boards>

[0071] The modified naphthol resin of the above embodiment can be dissolved and mixed with other components in a suitable solvent to form a resin varnish, and a copper foil substrate can be produced by a conventional method. For example, the resin composition of the above embodiment can be dissolved in a suitable solvent to form a resin varnish, which can be used to produce a copper foil substrate.

[0072] The copper foil substrate is manufactured as follows.

[0073] After impregnating 2116 glass fiber cloth with the above resin varnish, it was dried at about 170°C (impregnation machine temperature) for several minutes, and the drying time was adjusted and controlled to obtain a dried prepreg with a melt viscosity of about 4000 poise to 12000. Then, four prepregs were laminated between two copper foils with a thickness of about 35 μm, and a pressing process was performed (details will be described later) to form the copper foil substrate of this embodiment.

[0074] The conditions and steps of the pressing process are as follows:

[0075] Step 1: The temperature was increased from about 80° C. to about 195° C. at a rate of about 0.5 hours (can be recorded as 85→195° C., 0.5 hours).

[0076] Step 2: Increase the pressure to about 7 kg / cm for about 0.5 hours. 2 from about 25kg / cm 2 (7→25kg / cm 2 , can be recorded as 0.5 hours)

[0077] Step 3: Press at a temperature of about 195°C and a pressure of about 25 kg / cm 2 The test was carried out at a pressure of 195°C / 25kg / cm for approximately 2.0 hours. 2 , recorded as 2.0 hours).

[0078] <Preparation example of modified naphthol resin>

[0079] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples in any way.

[0080] <Example 1-1>

[0081] About 100 g of commercially available unmodified naphthol resin (trade name ResiCare® 4000, manufactured by Shanghai Hengfeng New Materials Technology Co., Ltd., agent of Suiye Industry; including the unmodified naphthol resin shown in [Formula 1]) was taken. Its hydroxyl value (also called OH value) was about 141. The hydroxyl value can be calibrated using commonly used standards (e.g., including but not limited to ISO 4629-2:2016, ASTM E222-10, GB / T 12008.3, CNS 6681). Next, about 100 g of the unmodified naphthol resin and about 113 g of 4-chloromethylstyrene were placed in a reaction vessel of suitable capacity and diluted with an appropriate amount of toluene until the solid content was about 30% by weight of the reactants (i.e., the unmodified naphthol resin and chloromethylstyrene). Here, the amount of toluene used was about 498 g. Additionally, about 1 g of tetrabutylammonium bromide (which can be used as a catalyst) was placed in the reaction vessel.

[0082] The reactants (i.e., the toluene solution of unmodified naphthol resin and chloromethylstyrene dissolved therein, but not limited to complete dissolution, including tetrabutylammonium bromide catalyst) were stirred with a suitable stir bar and heated to approximately 70°C.

[0083] The reactants were heated to about 70° C. with stirring, and then about 50% by weight of an aqueous solution of sodium hydroxide was continuously added dropwise over about 2 hours up to a total of about 68 g while continuing to stir at a constant temperature (about 70° C.).

[0084] After the dropwise addition was completed, the reaction was continued for about 4 hours with stirring at a constant temperature (about 70°C).

[0085] After the reaction, the reaction solution was poured into about 5 times the amount of methanol solution to precipitate the product. The precipitated product can be collected by filtration. After washing with methanol and water several times, a modified naphthol resin represented by [Formula 8] can be obtained, the corresponding number is A1, and it can be abbreviated as A1 modified resin.

[0086] <Example 1-2>

[0087] It was prepared in the same steps as in <Example 1-1>. The difference was that the relative amounts of chloromethylstyrene and naphthol resin were adjusted. Specifically, in <Example 1-1>, the number of moles of chloromethylstyrene was 1.05 times the total number of moles of hydroxyl groups in the naphthol resin (which can be recorded as an equivalent ratio of 1.05). In <Example 1-2>, the number of moles of chloromethylstyrene was 1.07 times the total number of moles of hydroxyl groups in the naphthol resin (which can be recorded as an equivalent ratio of 1.07).

[0088] By the method of <Example 1-2>, a modified naphthol resin represented by [Formula 8] can be produced, the corresponding number of which is A2, and this can be abbreviated as A2 modified resin.

[0089] The A1 modified resin and the A2 modified resin are structurally similar, except that the chain length distribution of the product is slightly different due to the difference in the corresponding equivalent weight during preparation, which can be determined by the polydispersity index described below.

[0090] <Example 1-3>

[0091] About 100 g of the same unmodified naphthol resin as used in <Example 1-1> was obtained. Then, about 100 g of the unmodified naphthol resin was placed in a reaction vessel of an appropriate capacity and diluted with an appropriate amount of toluene until at least completely dissolved. Here, the amount of toluene used was about 498 g. In addition, about 1 g of tetrabutylammonium bromide (which can be used as a catalyst) was placed in the reaction vessel. During the process of adding the unmodified naphthol resin, toluene, and / or tetrabutylammonium bromide, stirring was performed using an appropriate stirrer, and the mixture was heated to about 70°C.

[0092] After heating to about 70°C, about 68 g of about 50 wt% aqueous sodium hydroxide solution was directly added at a constant temperature (about 70°C) and reacted for about 1 hour with continuous stirring to produce a chlorinated naphthol resin represented by [Formula 2].

[0093] Then, about 4.37 g of methacrylic anhydride (eg, [Formula 6]) was continuously added dropwise over about 1 hour to a total of about 68 g, while continuing to stir and maintaining a constant temperature (about 70° C.) during the process.

[0094] After the dropwise addition was completed, the reaction was continued for about 10 hours while continuing stirring at a constant temperature (about 70°C).

[0095] After the reaction, the reaction solution was poured into about 5 times the amount of methanol solution to precipitate the product. The precipitated product can be collected by filtration. After washing with methanol and water several times, a modified naphthol resin represented by [Formula 9] can be obtained, the corresponding number is A3, and it can be abbreviated as A3 modified resin.

[0096] <Example 1-4>

[0097] It was prepared in the same steps as <Example 1-3>. The difference was that the relative amounts of methacrylic anhydride and naphthol resin were adjusted. Specifically, in <Example 1-3>, the number of moles of methacrylic anhydride was 1.05 times the total number of moles of hydroxyl groups in the naphthol resin (which can be recorded as an equivalent ratio of 1.05). In <Example 1-4>, the number of moles of methacrylic anhydride was 1.07 times the total number of moles of hydroxyl groups in the naphthol resin (which can be recorded as an equivalent ratio of 1.07).

[0098] By the method of <Example 1-4>, a modified naphthol resin represented by [Formula 9] can be produced, the corresponding number of which is A4, and can be abbreviated as A4 modified resin.

[0099] The A3 modified resin and the A4 modified resin are structurally similar, except that the chain length distribution of the product is slightly different due to the difference in the corresponding equivalent weight during preparation, which can be determined by the polydispersity index described below.

[0100] The resulting modified naphthol resin was evaluated by the following methods, and the results are shown in Table 1.

[0101] [Table 1]

[0102] <Evaluation method>

[0103] Hydroxyl conversion rate: It can be obtained by comparing the hydroxyl value of the reactant before the reaction with the hydroxyl value of the product after the reaction. For example, if the hydroxyl value of the reactant before the reaction is about 141 and the hydroxyl value of the product after the reaction is about 0.3, the hydroxyl conversion rate is about 99.8 (calculation formula: 1-0.3 / 141≒99.8%). The closer the hydroxyl conversion rate is to 100%, the more hydroxyl groups have been converted.

[0104] Number average molecular weight (Mn): The modified naphthol resin thus prepared was dissolved in tetrahydrofuran (THF) to prepare a test solution having a concentration of 1% by weight. The number average molecular weight of the test solution was then measured by gel permeation chromatography (GPC).

[0105] Weight average molecular weight (Mw): The modified naphthol resin thus prepared was dissolved in tetrahydrofuran (THF) to prepare a test solution having a concentration of 1% by weight. The weight average molecular weight of the test solution was then measured by gel permeation chromatography (GPC).

[0106] Polydispersity Index (PDI): The measured weight average molecular weight was divided by the measured number average molecular weight (i.e., Mw / Mn) to obtain the polydispersity index (PDI). The smaller the PDI, the more concentrated the molecular weight distribution. Under the same or similar conditions of initial reactants, catalysts, and their corresponding amounts, the smaller the PDI, the smaller the corresponding possibility of side reactions, and the more concentrated the molecular weight distribution. Therefore, when the molecular weight distribution is more gentle (i.e., PDI is small), the functional groups, morphology, and / or structure are more uniform, and a more uniform reaction / synthesis is achieved. In addition, when the molecular weight distribution is more gentle (i.e., PDI is small), the proportion of side reaction products (such as large polymer molecules formed by repolymerization) may also be relatively smaller. Therefore, in terms of product application, it may be more stable for subsequent processing or application, and the quality or productivity of the subsequent processed products may be improved.

[0107] Residual monomer: The remaining ratio of unreacted chloromethylstyrene (<Example 1-1> or <Example 1-2>) or unreacted methacrylic anhydride (<Example 1-3> or <Example 1-4>) can be measured and estimated by an appropriate quantitative method (such as, but not limited to, titration analysis or spectral analysis), and the remaining ratio can be estimated.

[0108] <Application examples and comparison examples for copper foil substrates>

[0109] Resin varnish compositions were prepared according to the blending ratios shown in Tables 2 and 3, and copper foil substrates were produced by the above-mentioned method.

[0110] The blend compositions of <Comparative Example>, <Example 2-1>, <Example 2-2>, <Example 2-3>, <Example 2-4>, and <Example 2-5> include corresponding base blends and additive blends. The weight percentage (wt%) of each component included in the base blends can be shown in [Table 2] and [Table 3]. Each component in the additive blend was added based on the total weight of the base blend. Taking <Comparative Example> as an example, if the weight of the base blend is 100 parts by weight, the additive blend contains 30 parts by weight of flame retardant, which can be counted as 30 PHR (parts per 100 parts of resin), and 60 parts by weight of flame retardant can be counted as 60 PHR.

[0111] In the Comparative Example, a commercially available polyphenylene ether resin, MX-90 resin manufactured by Saudi Basic Industries Co. (SABIC), was used.

[0112] The BMI used in <Comparative Example>, <Example 2-1>, <Example 2-2>, <Example 2-3>, <Example 2-4>, and <Example 2-5> is the same, and may be a commercially available BMI-70 series bismaleimide (BMI) resin sold by Nippon Keiki Kasei Co., Ltd.

[0113] The synthetic rubber used in <Comparative Example>, <Example 2-1>, <Example 2-2>, <Example 2-3>, <Example 2-4>, and <Example 2-5> is the same, and may be a commercially available SBS rubber sold by Nippon Soda Co., Ltd.

[0114] The flame retardant used in <Comparative Example>, <Example 2-1>, <Example 2-2>, <Example 2-3>, <Example 2-4>, and <Example 2-5> is the same, and may be a commercially available OP935 series flame retardant sold by Clariant AG.

[0115] The inorganic filler used in <Comparative Example>, <Example 2-1>, <Example 2-2>, <Example 2-3>, <Example 2-4>, and <Example 2-5> is the same, and may be a commercially available 525ARI series silica filler sold by Sibelco.

[0116] [Table 2]

[0117] [Table 3]

[0118] <Evaluation method>

[0119] a. Glass transition temperature (Tg)

[0120] Similarly to the above method, the glass transition temperature (Tg) of the film formed from the resin composition of the above formula was measured by a dynamic mechanical analyzer (DMA).

[0121] b. Coefficient of Thermal Expansion (CTE)

[0122] Similar to the above method, the coefficient of thermal expansion (CTE) of a film formed from the resin composition of the above formula was measured by a thermomechanical analyzer (TMA) at a heating rate of about 20° C. / min.

[0123] c. Peel strength

[0124] Similarly to the above method, the peel strength of the film formed from the resin composition having the above formulation was measured using a universal tensile tester in accordance with IPC-TM-650, method 2.4.8.

[0125] d. Water absorption

[0126] A square test piece measuring 5 cm x 5 cm was taken and placed in an oven at about 105°C for an appropriate measurement time (for example, about 2 hours), and then placed in a pressure cooker. The atmospheric conditions in the pressure cooker were about 2 atm x 120°C. After placing the test piece in the pressure cooker for about 120 minutes, the water absorption rate was calculated by dividing the weight difference of the test piece before and after placing it in the pressure cooker by the initial weight of the test piece x 100%.

[0127] e. Heat resistance

[0128] The test method was to immerse the pressure cooker test piece in a soldering furnace at 288±5°C and observe. If no delamination was observed, the heat resistance was recorded as "OK".

[0129] f. Dielectric constant (Dk)

[0130] Dielectric constant test: The test method was to bake a test piece of about 5cm x 5cm square of the copper foil board from which the copper foil had been removed in an oven at about 105°C for about 2 hours, and measure the thickness with a thickness meter.The test piece was then clamped to an impedance analyzer (Agilent E4991A) and the dielectric constant Dk data was measured at three points, and the average value was obtained.

[0131] g. Dielectric tangent (Df)

[0132] Dielectric loss tangent test: The test method was to bake a 5cm x 5cm test piece of the copper foil board from which the ketone foil had been removed in an oven at about 105°C for about 2 hours, and measure the thickness with a thickness meter.Then, the piece was clamped to an impedance analyzer (Agilent E4991A) and the dielectric loss tangent Df data was measured at three points, and the average value was obtained.

[0133] <Evaluation Results>

[0134] As can be seen from the experimental results in Tables 2 and 3, in <Example 2-1> to <Example 2-5>, by using the modified naphthol resin of the present invention, the heat resistance is improved, the thermal expansion coefficient is lowered, and the adhesive strength is increased. In addition, the low moisture absorption standard of a general copper clad laminate (CCL) is satisfied. Furthermore, Dk and Df also meet the dielectric level of a general copper foil board (for example, Df was a very low loss level of 0.0030 to 0.0065).

[0135] Furthermore, compared to when conventional resins (such as polyphenylene ether resins used in the manufacture of general copper foil boards) are used, other properties are equivalent to or within the range of the corresponding standard specifications. [Industrial Applicability]

[0136] In addition, the modified naphthol resin according to the above embodiment of the present invention may be directly or indirectly applied to a copper foil substrate and further processed into other electronic elements or products (such as circuit boards and copper foil substrates) for daily life, industry, or other suitable applications.

Claims

1. subjecting naphthol resin to salification and chemical grafting to form a modified naphthol resin having terminal alkenyl groups in its structure; A method for producing a modified naphthol resin, wherein a reagent used in the chemical grafting reaction has a terminal alkenyl group.

2. The method for producing a modified naphthol resin according to claim 1, wherein the naphthol resin has a structure represented by the following formula 1. 【Chemistry 1】 In formula 1, n is a positive integer from 2 to 40.

3. The method for producing a modified naphthol resin according to claim 1, wherein the electrophile used in the chemical grafting reaction is a halide, a halogenated alkene, or an alkenoic acid anhydride.

4. The method for producing a modified naphthol resin according to claim 3, wherein the electrophile is halomethylstyrene, acrylic anhydride, methacrylic anhydride, or methacryloyl chloride.

5. A modified naphthol resin having a structure represented by the following formula 3. 【Chemistry 2】 In formula 3, V is a vinyl group, an allyl group, or an isopropenyl group. L is a linking group having a double bond, n is a positive integer from 2 to 40.

6. The modified naphthol resin according to claim 5, wherein L is a ketone group.

7. 6. The modified naphthol resin according to claim 5, wherein L is a methylbenzyl group substituted with an alkyl group or an unsubstituted methylbenzyl group.

8. It is formed by a method of subjecting naphthol resin to a salification and chemical grafting reaction to form a modified naphthol resin having terminal alkenyl groups in the structure, The modified naphthol resin according to claim 5, wherein the reagent used in the chemical grafting reaction has a terminal alkenyl group.

9. A resin composition comprising a modified naphthol resin having a structure represented by the following formula 3: 【Chemistry 3】 In formula 3, V is a vinyl group, an allyl group, or an isopropenyl group. L is a linking group having a double bond, n is a positive integer from 2 to 40.

10. An electronic device comprising a film layer formed from a resin composition containing a modified naphthol resin having a structure represented by the following formula 3: 【Chemistry 4】 In formula 3, V is a vinyl group, an allyl group, or an isopropenyl group. L is a linking group having a double bond, n is a positive integer from 2 to 40.

Citation Information

Patent Citations

  • Active ester resin and resin composition thereof

    CN111393594A

  • Curable resin composition for coating, multilayer printed circuit board, printed circuit board, and dry film

    JP2004027145A

  • Curable resin composition, its cured product, new epoxy resin, and its production method

    JP2009286949A

  • Method for producing cured product of thermosetting resin composition and cured product obtained using the same

    JP2012102282A

  • Resin sheet and printed wiring board

    WO2021125121A1